Correlation between blood glucose and cerebrospinal fluid glucose levels in patients with differences in glucose metabolism - Tan, Qing Che; Xing, Xiao Wei; Zhang, Jia Tang; He, Mian Wang; Ma, Yu Bao; Wu, Lei; Wang, Xiaolin; Wang, Hong Fen; Yu, Sheng Yuan (Frontiers in Neurology, 2023)
Objectives: We aimed to determine a method to identify normal cerebrospinal fluid (CSF) glucose levels by examining the correlation between blood and CSF glucose levels in patients with normal and abnormal glucose metabolism. Methods: One hundred forty patients were divided into two groups according to their glucose metabolism. The glucose levels were obtained from CSF and fingertip blood at 6, 5, 4, 3, 2, 1, and 0 hours before lumbar puncture. SPSS 22.0 software was used for the statistical analysis. Results: In both the normal and abnormal glucose metabolism groups, CSF glucose levels increased with blood glucose levels at 6, 5, 4, 3, 2, 1, and 0 hours before lumbar puncture. In the normal glucose metabolism group, the CSF/blood glucose ratio range was 0.32–0.95 at 0–6 hours before lumbar puncture, and the CSF/average blood glucose ratio range was 0.40–0.74. In the abnormal glucose metabolism group, the CSF/blood glucose ratio range was 0.25–1.2 at 0–6 hours before lumbar puncture, and the CSF/average blood glucose ratio range was 0.33–0.78. Conclusions: The CSF glucose level is influenced by the blood glucose level 6 hours before lumbar puncture. In patients with normal glucose metabolism, direct measurement of the CSF glucose level can be used to determine whether the CSF level is normal. However, in patients with abnormal or unclear glucose metabolism, the CSF/average blood glucose ratio should be used to determine whether the CSF glucose level is normal.